Implementasi Kearifal Lokal Gusjigang dalam Mengoptimalkan Profil Pelajar Pancasila di SMP 2 Mejobo Kudus - Andrian Failani; Rondli Shokib Wawan (ILUMINASI: Journal of Research in Education, 2023)
This research aims to internalize the values and philosophy of Gusjigang into an independent curriculum and optimize it in the Pancasila Student Profile Strengthening Project (P5) at SMP 2 Mejobo Kudus. The background of this research is the low interest of teenagers in local wisdom and its implementation in everyday life. The influence of globalization also shows symptoms of the younger generation being more interested in and fond of foreign cultures, so it is feared that local wisdom values can be displaced by global values. SMP 2 Mejobo Kudus is committed to appreciating Gusjigang local wisdom and incorporating Gusjigang values into the school curriculum. This research is descriptive qualitative with data collection techniques including observation, interviews, and document analysis. The result of the research is that SMP 2 Mejobo has internalized the Gusjigang philosophy of Sunan Kudus's legacy into the school curriculum. The purpose of implementing Gusjigang values and philosophies into the curriculum is so that students have spiritual intelligence, social intelligence, and independence in entrepreneurship. The form of internalization of Gusjigang values is: The value of Gus "Good" is included in the moral education curriculum, the value of Ji "Ngaji" is included in the spiritual knowledge education curriculum, and the value of Gang "Dagang" is included in the entrepreneurship education curriculum.